Community-Based Nutrition Mentorship in School Canteens to Enhance Healthy Eating Behavior and Metabolic Resilience among High School Students - Judiono; Gumilar, Mulus; Mahmudah, Umi; Eko Mulyo, Gurid Pramintarto; Suprihartono, Fred Agung; Widiastuti, Yuliati; Widiastuti, Nabilla Maheswari (Gaceta Médica de Caracas, 2026)
Introduction: Adolescence is a critical period for establishing long-term eating habits and preventing health problems, including metabolic disorders. In Indonesia, more teenagers are developing metabolic syndrome and early-onset Type 2 Diabetes, which is worrying. School canteens are essential places where kids learn to eat, but they often lack adequate nutrition guidance and expert support. This study developed and evaluated a new program that uses community-based mentorship to help teenagers improve their nutrition and eat healthier.